CaMKII Isoforms in Learning and Memory: Localization and Function - Zalcman, Gisela; Federman, Noel; Romano, Arturo (Frontiers in Molecular Neuroscience, 2018)
Calcium/calmoudlin-dependent protein kinase II (CaMKII) is a key protein kinase in neural plasticity and memory, as have been shown in several studies since the first evidence in long-term potentiation (LTP) 30 years ago. However, most of the studies were focused mainly in one of the four isoforms of this protein kinase, the CaMKIIα. Here we review the characteristics and the role of each of the four isoforms in learning, memory and neural plasticity, considering the well known local role of α and β isoforms in dendritic terminals as well as recent findings about the γ isoform as calcium signals transducers from synapse to nucleus and δ isoform as a kinase required for a more persistent memory trace.